2018
DOI: 10.5194/esurf-6-319-2018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grain size and rock composition on simulated rock weathering

Abstract: Abstract. Both chemical and mechanical processes act together to control the weathering rate of rocks. In rocks with micrometer size grains, enhanced dissolution at grain boundaries has been observed to cause the mechanical detachment of particles. However, it remains unclear how important this effect is in rocks with larger grains, and how the overall weathering rate is influenced by the proportion of high-and low-reactivity mineral phases. Here, we use a numerical model to assess the effect of grain size on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Although olivines are known to be more weathering-reactive than plagioclase and pyroxenes (Eggleton et al, 1987;Schwarz, 1997), these minerals present grossly similar weathering rates (Nesbitt and Wilson, 1992), no matter the grain size (Israeli and Emmanuel, 2018). This suggests no direct (or little) influence of differential mineral sensitivity on weathering rates and geochemical transfers on different volcanic rocks.…”
Section: Constraints To Differentiated Bauxitic Weathering In Highlanmentioning
confidence: 98%
“…Although olivines are known to be more weathering-reactive than plagioclase and pyroxenes (Eggleton et al, 1987;Schwarz, 1997), these minerals present grossly similar weathering rates (Nesbitt and Wilson, 1992), no matter the grain size (Israeli and Emmanuel, 2018). This suggests no direct (or little) influence of differential mineral sensitivity on weathering rates and geochemical transfers on different volcanic rocks.…”
Section: Constraints To Differentiated Bauxitic Weathering In Highlanmentioning
confidence: 98%
“…These surrounded elements are considered to be detached physically and their elements are also reassigned to the fluid phase (Figure 1; see also Supplementary Video S1). Israeli & Emmanuel (2018) used the model with different ratios of reactive and nonreactive minerals and found a nonlinear impact of mineral composition on rock weathering rates. However different patterns of discontinuities in rocks were not examined.…”
Section: Model Structurementioning
confidence: 99%
“…In studies focused on rock weathering at the submicron scale, enhanced dissolution at grain boundaries was shown to cause the mechanical detachment of particles into the fluid phase (Emmanuel & Levenson, 2014;Fischer & Luttge, 2017;Krklec et al, 2016;Silveira & Aarão Reis, 2013). Such chemo-mechanical rock weathering was observed in micritic limestone (Levenson & Emmanuel, 2016), however particle detachment can occur in various types of rocks with larger grain sizes and different mineral compositions (Israeli & Emmanuel, 2018;Krklec et al, 2013;Levenson & Emmanuel, 2016).…”
mentioning
confidence: 99%
“…3b). Studies have shown that coarser grain sizes are more susceptible to mechanical weathering via grain detachment induced by chemical weathering (Israelli and Emmanuel, 2018); thus, although care was taken, it is possible that the luminescence depth profile (likely <10 mm based on BALL02 and BALL03) was lost during sampling and/or sample preparation due to the presence of a fragile weathering crust, potentially with a sub-surface zone of weakness (e.g. Robinson and Williams, 1987).…”
Section: Luminescence Depth Profilesmentioning
confidence: 99%